Development and evaluation of a Chinese-language newborn needing hotline: A prospective cohort study - Livingstone Verity H; Janssen Patricia A; Chang Bruce; Klein Michael C (BMC, 2009)
Abstract Background Preference for formula versus breast feeding among women of Chinese descent remains a concern in North America. The goal of this study was to develop an intervention targeting Chinese immigrant mothers to increase their rates of exclusive breastfeeding. Methods We convened a focus group of immigrant women of Chinese descent in Vancouver, British Columbia to explore preferences for method of infant feeding. We subsequently surveyed 250 women of Chinese descent to validate focus group findings. Using a participatory approach, our focus group participants reviewed survey findings and developed a priority list for attributes of a community-based intervention to support exclusive breastfeeding in the Chinese community. The authors and focus group participants worked as a team to plan, implement and evaluate a Chinese language newborn feeding information telephone service staffed by registered nurses fluent in Chinese languages. Results Participants in the focus group reported a strong preference for formula feeding. Telephone survey results revealed that while pregnant Chinese women understood the benefits of breastfeeding, only 20.8% planned to breastfeed exclusively. Only 15.6% were breastfeeding exclusively at two months postpartum. After implementation of the feeding hotline, 20% of new Chinese mothers in Vancouver indicated that they had used the hotline. Among these women, the rate of exclusive breastfeeding was 44.1%; OR 3.02, (95% CI 1.78-5.09) compared to women in our survey. Conclusion Initiation of a language-specific newborn feeding telephone hotline reached a previously underserved population and may have contributed to improved rates of exclusive breastfeeding.